Kepuasan Kerja Pimpinan dalam Lingkungan Universitas Negeri Padang - Chichi Andriani; Kamaruddin - (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2012)
The objective of this research is to find characteristic of leader related to their work values in Padang State University in order to manage the academic process in Padang State University. The population of this research was all academic leaders in Padang State University. Then sample was consist of 75 academic leader’s in all of faculty in Padang State University. Survey about the influence of self awareness, motivation and machiavelism toward work value of the academic leader of Padang State University found that hard effort gives more influence rather than success value and this result shows that to build the leader work value it must be started from honesty, self confident and self evaluation of the academic leader of Padang State University, this factor will give more influence to increase ambition, doing the right thing and successfully. Motivation gives significant influence toward work value of academic leader of Padang State University. It is means to increase the leader work value should be started from the increase of motivation.